2021
DOI: 10.1111/jfpp.15890
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an oral processing model for three varieties of rice

Abstract: The objective of this study was to establish an oral processing model of cooked rice. Principal component analysis and orthogonal partial least squares discriminant analysis were performed to determine the main factors of cooked rice in different oral processing stages. The results of our study suggest that the textural properties and water content (dry wt basis) of the rice bolus are the main factors in determining the type of oral processing model. Specifically, the factors influencing the swallowing of Japo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The relaxation time of water analysis was carried out according to the method described in our previous research (Asimi et al., 2021). Briefly, 1.5 g rice samples were weighed and placed in a small transparent tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxation time of water analysis was carried out according to the method described in our previous research (Asimi et al., 2021). Briefly, 1.5 g rice samples were weighed and placed in a small transparent tube.…”
Section: Methodsmentioning
confidence: 99%
“…The rice texture properties were determined according to the method described in our previous research (Asimi et al., 2021; Wang et al., 2019). First, weigh 50 g rice, add 60 g distilled water, soak for 30 min at room temperature, and cook for 30 min to prepare cooked rice.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed results for the properties of the bolus are provided in Tables S1, S2, and S4. According to other methods Asimi et al (2021), in order to obtain the degree of structure comprehensive evaluation function, PCA analysis was carried out on the changing structural parameters such as hardness, adhesiveness force, adhesiveness, cohesiveness, springiness, gumminess, chewiness, and particle size, with different saliva addition during in vitro mastication. The results of the Kaiser-Meyer-Olkin (KMO) measure and Bartlett's sphericity test of structural parameters in the PCA analysis are showed in Table 1.…”
Section: The Influence Of Saliva Addition During In Vitro Masticationmentioning
confidence: 99%
“…In our previous studies, the influence of mastication on cooked rice boluses was quantified by changes in physical characteristics, such as water content (Liu, Ren, Asimi, Peng, & Zhang, 2020), particle size, texture, and rheology. In vivo mastication results have shown that the factors influencing the swallowing of Japonica rice include mastication time, mastication number, cohesiveness, and water content (dry wt basis) (Asimi et al, 2021). During the whole mastication process, the average saliva secretion for cooked rice was 300 mg/g, and the average mastication time was 20 s. However, in vivo mastication experiments cannot control the amount of saliva secretion, and it is impossible to investigate the influence of the amount of saliva on the microstructure and physical properties of rice bolus.…”
mentioning
confidence: 99%